Factors responsible for the limited inland extent of sand deposits on Leyte Island during 2013 Typhoon Haiyan. Issue 4 (4th April 2017) - Watanabe, M.; Bricker, J. D.; Goto, K.; Imamura, F.
Abstract: Previous geological studies suggest that the maximum inland extent of storm‐induced sand deposits is shorter, but their thickness is larger, than those of tsunami‐induced sand deposits. However, factors that determine the maximum extent and thickness of storm deposits are still uncertain. We conducted numerical simulations of storm surge, waves, and sediment transport during Typhoon Haiyan in order to understand the distribution and sedimentary processes responsible for storm deposits. Numerical results showed that wave‐induced currents slightly offshore were strong, but attenuated rapidly in the inland direction after wave breaking. Therefore, sediments were not transported far inland by waves and storm surge. Consequently, the maximum inland extent of storm deposits was remarkably shorter than the inland extent of inundation. We also revealed that vegetation (roughness coefficient) and typhoon intensity greatly affect the calculation of maximum extent and thickness distribution of storm deposits. As the duration of wave impact on a coast is relatively long during a storm (hours, compared to minutes for a tsunami), sediments are repeatedly supplied by multiple waves. Therefore, storm deposits tend to be thicker than tsunami deposits, and multiple layers can form in the internal sedimentary structure of the deposits. We infer that limitation of the sand deposit to within only a short distance inland from the shoreline and multiple layers found in a deposit can be used as appropriate identification proxies for storm deposits. Key Points: Flow velocity over land due to waves and storm surge is small, so that maximum inland extent of storm deposit is short The distribution of sand deposits is heavily affected by wave intensity and the roughness coefficient over land Useful proxies for identifying storm deposits are their limited inland extent and the presence of multiple layers